The Tour de France: a physiological review - Lucia, A.; Earnest, C.; Arribas, C. (Scandinavian Journal of Sports Science, 2003)
On 5 July 2003, the Tour de France (TDF) has celebrated 100th running. Instead of a chimney sweep competing during his free time (as in 1903), the recent winner is a highly trained, professional cyclist whose entire life-style has been dedicated to reach his pinnacle during this event. The TDF has been held successfully for 100 years, but the application of the physiologic sciences to the sport is a relatively recent phenomenon. Although some historical reports help to understand the unique physiological characteristics of this race, scientific studies were not available in Sports Science/Applied Physiology journals until the 1990s. The aim of this article is to review the history of the TDF. Special emphasis is placed on the last decade where classic physiology has been integrated into applied scientific cycling data.